IB - "Enrico, Roger" (New York, 1986)
The inside story of the recent business war from the president of the company that shook the foundations of the way American corporations merchandise their products by forcing Coke into the biggest marketing blunder of the century
Keywords: "Associations, Institutions etc, United states"